Разработка портативного устройства для распознавания образов - Резник, М. В. (ХНУРЕ, 2019)
Following work is devoted to developing software and hardware parts for a portable device used for pattern recognition. To meet hardware requirements and follow the criteria of mobility and low space used, the choice of device came to Raspberry Pi 3 B. For device to provide required functionality of capturing images and sending them for further processing, while being applicable for on-the-go use, different official modules and additional hardware were used, such as: camera module, Wi-Fi module, USB cable, power bank. After being captured, images are sent to a host application via internet, where they are processed to detect the preassigned object using Deep Learning methodology.